2017
DOI: 10.1038/s41598-017-10963-1
|View full text |Cite
|
Sign up to set email alerts
|

Probe-based confocal laser endomicroscopy for in vivo evaluation of the tumor vasculature in gastric and rectal carcinomas

Abstract: Probe-based Confocal Laser Endomicroscopy (pCLE) is a powerful imaging technique that allows to perform gastrointestinal endomicroscopy at subcellular resolution. The aim of this study was to assess the use of pCLE to evaluate tumor angiogenesis in rectal and gastric cancers. A total of 35 consecutive patients with gastric and 91 with rectal carcinomas underwent endoscopy and pCLE during the same examination. Vascular assessment was based on vessel shape and size, vessel permeability and blood flow, and allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…To this end patients affected by gastric cancer were injected with fluorescein and tumor vascularization was assessed by probe-based confocal laser endomicroscopy (pCLE) during the gastric endoscopy procedure. As previously demonstrated this procedure allows the in vivo evaluation of different parameters affecting vascular efficiency such as vessel diameter, tortuosity, leakiness and vessels defective flow [55,56]. The results of the analyses performed on a representative patient are reported in Figure 1 and the relative video in Supplemental Video S1.…”
Section: Resultsmentioning
confidence: 98%
“…To this end patients affected by gastric cancer were injected with fluorescein and tumor vascularization was assessed by probe-based confocal laser endomicroscopy (pCLE) during the gastric endoscopy procedure. As previously demonstrated this procedure allows the in vivo evaluation of different parameters affecting vascular efficiency such as vessel diameter, tortuosity, leakiness and vessels defective flow [55,56]. The results of the analyses performed on a representative patient are reported in Figure 1 and the relative video in Supplemental Video S1.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, both GC tumor and stromal cells produce various angiogenic factors, including VEGF, IL-8, and platelet-derived endothelial cell growth factor (PD-ECGF). Tumor angiogenesis plays an essential role in growth, invasion, and metastatic spread of GC [ 96 ], indicating that pharmacologic blockade of angiogenesis is a promising new therapy, and that the real-time assessment of the vasculature status is a promising approach to predict the efficacy of the treatments and improve the clinical management of patients with GC [ 97 ]. Indeed, high levels of angiogenic factors in serum and tumors are associated with worse outcomes in GC patients.…”
Section: Gastric Cancer and Its Tmementioning
confidence: 99%
“…Recent investigations have demonstrated that fluorescein leakage reflects microcirculatory disturbances and is considered to be an important finding to identify malignant lesions or inflammatory mucosa of ulcerative colitis. [25][26][27] The present study has several limitations. Firstly, this is a pilot study and it is difficult to draw a solid conclusion; nevertheless, it highlights the potential dose reduction of IV fluorescein during pCLE.…”
Section: Discussionmentioning
confidence: 86%